PRIORITY IMPROVEMENT OF SEA TRANSPORTATION SERVICES KMP DHARMA RUCITRA VII ROUTE SURABAYA – LABUAN BAJO - Nika Devi Permata Wijaya; Zaid Dzulkarnain Zubizaretta; Yoseph Kalasanso (Universitas Islam Malang, 2023)
Sea transportation is an important mode of transportation and is widely used by the people of Indonesia to connect between islands and areas throughout their territory. PT. Dharma Lautan Utama (DLU) is a ferry transportation service company and manager of ferry ports for passengers, vehicles, and goods. To improve the quality of service, a priority step for improvement is prepared which refers to the standards and weaknesses of the service. By using the AHP method, an analysis related to the prioritization of the 6 selected stakeholders is obtained as follows: service improvement criteria which include Safety, Security, Comfort, Convenience, and Regularity obtained the highest priority value on Departure Schedule Improvement of 34% by improving service related to the accuracy of the departure schedule by giving repeated socialization of information or pasting information as clearly as possible, then followed by an increase in Compliance and Passenger Safety Standards of 19%, Shipping Frequency of 17%, Load Factor of 11%, Shipping Costs of 10%, and finally Law Enforcement of 9%. Keywords: AHP; Service Improvement; Sea Transportation.